Pengaruh Pengangaran Berbasis Kinerja, Pengawasan Preventif Dan Pengawasan Fungsional Terhadap Efektifitas Pengendalian Anggaran Keuangan Daerah (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Grobogan) - Nugroho, Lilik Singgih (2016)
Effectiveness of budgetary control are the objectives of the budget as a means of controlling functions. To achieve effective control of the budget it needs an oversight on the budget. This study aims to examine the influence of performance-based budgeting, preventive supervision and functional supervision of the effectiveness of local financial budget control in the Region Performance Unit Grobogan. The population in this study were all employees working at the regional work units (SKPD) Grobogan. Method of this research is a survey method using a questionnaire. The sample used in this study amounted to 98 respondents. In this study, data analysis tools used are multiple regression test. The results of the analysis in this study showed: 1) Performance-based Budgeting positive and significant impact on the effectiveness of budgetary control. So the better the performance-based budgeting, the higher the effectiveness of budgetary control. 2) preventive supervision does not affect the effectiveness of budgetary control. So increasing the effectiveness of supervision of preventive budgetary control is also increased. 3) Monitoring functional positive and significant impact on the effectiveness of budgetary control. So the higher the intensity, the functional supervision encourages internal watchdog to improve the effectiveness of budget control. Keywords : effectiveness of local financial budget control, functional supervision, supervision of preventive, performance-based budgeting